Job Insecurity dalam Organisasi - Rony Setiawan; Bram Hadianto (Jurnal Manajemen Maranatha, 2008)
The phenomenon of job insecurity is not a new term in business organization environment. Job insecurity is the condition which the employees feel threated by uncertainty of sustainability in working at their organizations. Appearance of job insecurity will cause negative impact to employees physically and psychologically both in short term and long term. However, in fact, not all organizations aware about this significant effect of it toward employee specifically and organization generally. Then, what is the importance of managing job insecurity in employment relationship? This article aims to explain the effect of job insecurity in one organization and how the company should manage this situation, in an employment relationship context.